2021
DOI: 10.47371/mycosci.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

<i>Neoboletus infuscatus</i>, a new tropical bolete from Hainan, southern China

Abstract: With the development of molecular techniques, several new species were discovered. In addition, some species were reassessed and new genera were established to accommodate certain taxa in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The island is famous for its rich biological resources and has at least 397 endemic plant species (Francisco-Ortega et al, 2010;Lu et al, 2011;Jiang et al, 2013;Chen, 2014). Recent publications also have shown that the island has a high diversity of fungi (Zeng et al, 2014;An et al, 2017;Wu et al, 2019;Jiang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The island is famous for its rich biological resources and has at least 397 endemic plant species (Francisco-Ortega et al, 2010;Lu et al, 2011;Jiang et al, 2013;Chen, 2014). Recent publications also have shown that the island has a high diversity of fungi (Zeng et al, 2014;An et al, 2017;Wu et al, 2019;Jiang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of molecular technology, molecular methods have been continuously applied to the taxonomy, systematics, phylogeny and biogeography of macrofungi, and the classification of boletes has made unprecedented progress. Since 2016, more than 100 new species from China have been described [ 1 , 2 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], but few of them have been reported in Jiangxi Province [ 2 , 36 , 38 , 44 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%